2022
DOI: 10.1097/aci.0000000000000853
|View full text |Cite
|
Sign up to set email alerts
|

Is immunotherapy safe for treatment of severe asthma

Abstract: Purpose of reviewThe benefits of allergen immunotherapy (AIT), including subcutaneous allergen immunotherapy (SCIT) and sublingual allergen immunotherapy (SLIT), for IgE-mediated asthma are well established, especially for dust mite. This review will explore whether the benefits of AIT outweigh the risks in severe asthmatic patients.Recent findingsStudies have mostly included mild and moderate asthmatic patients, but at least a few studies do show improvements in asthma symptoms and medication use in severe as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Asthma biologics, especially Omalizumab, had been reported that it could improve outcomes in severe, controlled asthmatic patients with SCIT ( 20 ). In our study the application of Omazumab before treatment was associated with a decreased risk of immediate LRs in maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma biologics, especially Omalizumab, had been reported that it could improve outcomes in severe, controlled asthmatic patients with SCIT ( 20 ). In our study the application of Omazumab before treatment was associated with a decreased risk of immediate LRs in maintenance phase.…”
Section: Discussionmentioning
confidence: 99%
“…Where sensitisation to certain allergens is proven, subcutaneous or sublingual immunotherapy has been shown to be efficacious in children and adults for both allergic rhinitis and asthma [40][41][42][43], although safety and efficacy evidence is less clear in severe asthma [44]. Biologic therapies such as anti-IgE, anti-IL-5/5R and anti-IL-4/13R are not indicated in allergic rhinitis but can provide benefit when administered for treatment of severe asthma.…”
Section: Allergic Rhinitis Chronic Rhinosinusitis and Nasal Polyposismentioning
confidence: 99%